Cold plasma: a promising technology for improving the rheological characteristics of food - R. Kaavya (2022)
At the beginning of the 21st century, many consumers show interest in purchasing safe, healthy, and nutritious foods. The intent requirement of end-users and many food product manufacturers are trying to feature a new processing technique for the healthy food supply. The non-thermal nature of cold plasma treatment is one of the leading breakthrough technologies for several food processing applications. The beneficial response of cold plasma processing on food quality characteristics is widely accepted as a substitution technique for new food manufacturing practices. This review aims to elaborate and offer crispy innovative ideas on cold plasma application in various food processing channels. It highlights the scientific approaches on the principle of generation and mechanism of cold plasma treatment on rheological properties of foods. It provides an overview of the behavior of cold plasma in terms of viscosity, crystallization, gelatinization, shear stress, and shear rate. Research reports highlighted that the cold plasma treated samples demonstrated a pseudoplastic behavior. The published literatures indicated that the cold plasma is a potential technology for modification of native starch to obtain desirable rheological properties. The adaptability and environmentally friendly nature of non-thermal cold plasma processing provide exclusive advantages compared to the traditional processing technique.